Backstepping Controller With Dual Self-Tuning Filter for Single-Phase Shunt Active Power Filters Under Distorted Grid Voltage Condition - Jayasankar, V. N.; Vinatha, U. (IEEE transactions on industry applications, 2020)
This article presents the design and hardware implementation of an adaptive nonlinear controller for fast, robust, and stable control of single-phase shunt active power filter. The proposed control system consists of two control loops: an inner harmonic current compensation loop and an outer dc-voltage control loop. The inner loop is realized using self tuning filter based instantaneous power theory (pq theory). The limitations of conventional low-pass filter based fundamental component extraction methods are overcome using self-tuning filter. The outer loop is realized backstepping controller (BSC). The limitations observed in existing dc-link voltage controllers like poor stability margin, steady state error, chattering problem, etc., are overcome by the proposed BSC. The switching loss estimation is introduced in BSC using design estimation rules to enhance the dc-link loss compensation capability. The stability of the system with the proposed controller is studied using Barbalat lemma. A laboratory prototype of BSC based shunt active power filter is implemented. The control algorithm is implemented in a single all on chip field programmable gate array (FPGA). To ensure the effectiveness of the controller in mitigating the harmonic currents and controlling dc-link voltage, the control algorithm is tested under steady state and dynamic conditions.